Nature of magnetism in Ca3Co2O6 - Wu, Hua; Haverkort, Maurits W. (Arxiv, 2005)
We find using LSDA+U band structure calculations that the novel one-dimensional cobaltate Ca$_3$Co$_2$O$_6$ is not a ferromagnetic half-metal but a Mott insulator. Both the octahedral and the trigonal Co ions are formally trivalent, with the octahedral being in the low-spin and the trigonal in the high-spin state. The inclusion of the spin-orbit coupling leads to the occupation of the minority-spin